T cell receptor engineering of primary NK cells to therapeutically target tumors and tumor immune evasion - Miranda H Meeuwsen; Laura T Morton; Tassilo L A Wachsmann; Anne K Wouters; Dennis F G Remst; Marleen M van Loenen; J H Frederik Falkenburg; Mirjam H M Heemskerk (Journal for ImmunoTherapy of Cancer)
Background T cell receptor (TCR)-engineered cells can be powerful tools in the treatment of malignancies. However, tumor resistance by Human Leukocyte antigen (HLA) class I downregulation can negatively impact the success of any TCR-mediated cell therapy. Allogeneic natural killer (NK) cells have demonstrated efficacy and safety against malignancies without inducing graft-versus-host-disease, highlighting the feasibility for an ‘off the shelf’ cellular therapeutic. Furthermore, primary NK cells can target tumors using a broad array of intrinsic activation mechanisms. In this study, we combined the antitumor effector functions of NK cells with TCR engineering (NK-TCR), creating a novel therapeutic strategy to avoid TCR-associated immune resistance.Methods BOB1, is a transcription factor highly expressed in all healthy and malignant B cell lineages, including multiple myeloma (MM). Expression of an HLA-B*07:02 restricted BOB1-specifc TCR in peripheral blood–derived NK cells was achieved following a two-step retroviral transduction protocol. NK-TCR was then compared with TCR-negative NK cells and CD8-T cells expressing the same TCR for effector function against HLA-B*07:02+ B-cell derived lymphoblastoid cell lines (B-LCL), B-cell acute lymphoblastic leukemia and MM cell lines in vitro and in vivo.Results Firstly, TCR could be reproducibly expressed in NK cells isolated from the peripheral blood of multiple healthy donors generating pure NK-TCR cell products. Secondly, NK-TCR demonstrated antigen-specific effector functions against malignancies which were previously resistant to NK-mediated lysis and enhanced NK efficacy in vivo using a preclinical xenograft model of MM. Moreover, antigen-specific cytotoxicity and cytokine production of NK-TCR was comparable to CD8 T cells expressing the same TCR. Finally, in a model of HLA-class I loss, tumor cells with B2M KO were lysed by NK-TCR in an NK-mediated manner but were resistant to T-cell based killing.Conclusion NK-TCR cell therapy enhances NK cell efficacy against tumors through additional TCR-mediated lysis. Furthermore, the dual efficacy of NK-TCR permits the specific targeting of tumors and the associated TCR-associated immune resistance, making NK-TCR a unique cellular therapeutic.